Evaluation of Concrete Compressive Strength with Coral Stone as a Fine Aggregate Replacement - Ibrahim, Ibrahim; Sulianti, Ika; Andini, Dita Putri; Sentosa, Riandi; Panjaitan, MM Lanny W; Lukas, Lukas (Universitas Negeri Padang, 2024)
This study examines the effect of using coral stone as a substitute for fine aggregate on the compressive strength of concrete. Tests were conducted with varying coral stone replacement percentages ranging from 0% to 100%. The results showed that coral stone can enhance the compressive strength of concrete, with an optimal replacement level of 80%, resulting in a 21.16% increase compared to normal concrete. However, replacements above 80% led to a decline in compressive strength, particularly at the 100% replacement level, which showed a 9.37% reduction in strength compared to normal concrete. This decrease was caused by increased porosity, varying aggregate quality, and an imbalance in the water-cement ratio, which disrupted the hydration process and microstructure formation of the concrete. Based on these findings, coral stone can be an effective alternative to replace fine aggregate such as sand, but its use should be limited to 80% to maximize the strength improvement without reducing performance.